Seasonal variations in the distribution of aliphatic hydrocarbons in surface sediments from the Selangor River, Peninsular Malaysia's West Coast - Magam, Sami M.; Masood, Najat; Alkhadher, Sadeq A. A.; Alanazi, Tahani Y. A.; Zakaria, Mohamad Pauzi; Sidek, Lariyah Mohd; Suratman, Suhaimi; Alrabie, Nabeel Abdullah (Springer, 2024)
The seasonal variation of petroleum pollution including n-alkanes in surface sediments of the Selangor River in Malaysia during all four climatic seasons was investigated using GC–MS. The concentrations of n-alkanes in the sediment samples did not significantly correlate with TOC (r = 0.34, p > 0.05). The concentrations of the 29 n-alkanes in the Selangor River ranged from 967 to 3711 µg g-1 dw, with higher concentrations detected during the dry season. The overall mean per cent of grain-sized particles in the Selangor River was 85.9 ± 2.85 sand, 13.5 ± 2.8 clay, and 0.59 ± 0.34 gravel, respectively. n-alkanes are derived from a variety of sources, including fresh oil, terrestrial plants, and heavy/degraded oil in estuaries. The results of this study highlight concerns and serve as a warning that hydrocarbon contamination is affecting human health. As a result, constant monitoring and assessment of aliphatic hydrocarbons in coastal and riverine environments are needed. © 2023, The Author(s), under exclusive licence to Springer Nature B.V.